ETHICAL INTEGRATION OF GENERATIVE AI IN ISLAMIC EDUCATION: TOWARD INCLUSIVE AND SUSTAINABLE HUMAN CAPITAL DEVELOPMENT - Mukaffan; Siswanto, Ali Hasan (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
Generative Artificial Intelligence (GenAI) is reshaping education, including Islamic contexts, while raising ethical, digital, and infrastructural concerns. This study explores how ethical and contextual integration of GenAI can drive inclusive and sustainable Islamic education reform. Through a systematic review of 85 high-impact articles, a three-layered framework is developed: technological infrastructure, human capability, and ethical governance. Key findings highlight the urgency of early AI literacy, adaptive teacher training, and fair, outcome-based evaluation. The proposed “GenAI-Integrated Islamic Learning Ecosystem” model maps the adoption from awareness to autonomy. This study bridges Islamic ethics, sociotechnical approaches, and human capital policy to offer strategic insights for ethical and empowering AI governance. Generative Artificial Intelligence (GenAI) telah mengubah ekosistem pendidikan, termasuk pendidikan Islam, namun memunculkan tantangan seperti kesenjangan keterampilan digital, ketimpangan infrastruktur, dan isu etika. Studi ini menganalisis integrasi GenAI secara etis dan kontekstual untuk mendukung reformasi pendidikan Islam yang inklusif dan berkelanjutan. Dengan systematic literature review terhadap 85 artikel, dikembangkan kerangka analitis tiga lapis: infrastruktur teknologi, kapabilitas manusia, dan tata kelola etis. Temuan menekankan pentingnya literasi AI sejak dini, pelatihan adaptif bagi pendidik, serta evaluasi berbasis keadilan. Model “Ekosistem Pembelajaran Islami Berbasis GenAI” ditawarkan sebagai peta evolusi adopsi AI. Studi ini menyinergikan etika Islam, pendekatan sosial-teknologis, dan kebijakan SDM sebagai kontribusi strategis bagi tata kelola AI yang manusiawi dan berkeadilan.